Independent association of PCSK9 with platelet reactivity in subjects without statin or antiplatelet agents - Wang, Shuai; Fu, Di; Liu, Huixing; Peng, Daoquan (Frontiers in Cardiovascular Medicine, 2022)
Background and aims Proprotein convertase subtilisin/kexin type 9 (PCSK9) levels could predict cardiovascular event in patients with well-controlled LDL-C levels, suggesting an LDL-independent mechanism of PCSK9 on the cardiovascular system. Accumulating evidence suggests PCSK9 might be associated with increased platelet reactivity. This study aimed to assess the relationship between PCSK9 levels and platelet reactivity in subjects not taking statins or antiplatelet agents. Methods A cross-sectional study was conducted to investigate the independent contribution of PCSK9 to platelet activity by controlling for the potential confounding factors. The study population included 89 subjects from a health examination centre who underwent routine annual health check-ups or had an examination before a selective operation. Subjects taking statins or antiplatelet agents were excluded. Adenosine diphosphate (ADP)-induced platelet aggregation was determined by PL-11 platelet analyzer using impedance aggregometry and plasma PCSK9 levels were determined using an ELISA. Serum Lipid profile was assessed by measuring the concentration of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and triglyceride (TG), with low-density lipoprotein cholesterol (LDL-C) being directly measured using enzymatic techniques. The association between PCSK9 and platelet reactivity was investigated. Results The study subjects were composed of 53 males and 36 females with an average age of 55 (±11) years old. The univariate correlation analysis showed significant correlation between ADP-induced maximal aggregation rate (MAR) and PCSK9 (r = 0.55, p < 0.001) as well as TC (r = 0.23, p = 0.028), LDL-C (r = 0.27, p < 0.001), and PLT (r = 0.31, p = 0.005). Being male (41.2% vs. 46.6, p = 0.04) and smoking (37.4 vs. 46.2%, p = 0.016) were associated with lower ADP-induced MAR than being female and non-smoking. However, there is no correlation between PCSK9 and AA-induced platelet maximal aggregation rate (r = 0.17, p = 0.12). Multiple regression analysis suggested that PCSK9 contributed independently to ADP-induced maximal aggregation rate (β = 0.08, p = 0.004) after controlling for the effect of TC, LDL-C, PLT, being male, and smoking. Conclusions PCSK9 is positively associated with platelet reactivity, which may partly account for the beneficial effect of PCSK9 inhibition in reducing the risk of major adverse cardiovascular events after acute coronary syndrome (ACS).